Cryptotermes camelus (Isoptera: Kalotermitidae), a new drywood termite species from the Bolivian Chaco - Scheffrahn, Rudolf H. (Zootaxa, 2021)
Cryptotermes Banks, 1906 is the third most diverse kalotermitid genus worldwide after Glyptotermes Froggatt, 1897 and Neotermes Holmgren, 1911, with its greatest diversity found in the Neotropics (Krishna et al. 2013a). Furthermore, the greatest number of species of Cryptotermes are known from the Caribbean Basin (Scheffrahn & Křeček 1999, Casala et al. 2016, Scheffrahn 2019). Although Araujo (1977) and Bacchus (1987) list Cryptotermes domesticus (Haviland, 1898) from Trinidad (treated as mainland) and Panama, respectively, Scheffrahn & Křeček (1999) and Scheffrahn et al. (2009) doubt the existence of this Asian species in the New World. Without C. domesticus, the total extant Neotropical diversity of Cryptotermes is 29 endemic and three exotic species (Constantino 2020).